2002
DOI: 10.1080/000163502760147981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial occlusal interferences depends on previous experience of temporomandibular disorders

Abstract: Studies on artificial interferences in subjects with no temporomandibular (TMD) history have shown adaptation to the interference within a fairly short period of time. The role of occlusal factors in the etiology of TMD has therefore been questioned. The results might have been different, however, if subjects with a prior TMD history had been included in the study groups. To test this assumption in a randomized double-blind clinical set-up, we included healthy women without (n = 26) as well as with (n = 21) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
10

Year Published

2012
2012
2045
2045

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 17 publications
2
61
0
10
Order By: Relevance
“…It should be kept in mind that this study was performed on healthy subjects (without present or passed history of TMD). It may be possible that patients suffering already from TMD react differently to an experimentally introduced occlusal interference due to a deficiency in their adaptation capacity (Le Bell et al 2002). This hypothesis is also based in the observation that TMD patients do keep their teeth in contact more often during daytime (Chen, 2005) and therefore are more likely to feel the interference as a disturbing factor (Le Cao et al 2009).…”
Section: Temporomandibular Disorders and Occlusionmentioning
confidence: 94%
See 1 more Smart Citation
“…It should be kept in mind that this study was performed on healthy subjects (without present or passed history of TMD). It may be possible that patients suffering already from TMD react differently to an experimentally introduced occlusal interference due to a deficiency in their adaptation capacity (Le Bell et al 2002). This hypothesis is also based in the observation that TMD patients do keep their teeth in contact more often during daytime (Chen, 2005) and therefore are more likely to feel the interference as a disturbing factor (Le Cao et al 2009).…”
Section: Temporomandibular Disorders and Occlusionmentioning
confidence: 94%
“…This hypothesis is also based in the observation that TMD patients do keep their teeth in contact more often during daytime (Chen, 2005) and therefore are more likely to feel the interference as a disturbing factor (Le Cao et al 2009). To test this assumption Le Bell et al (2002) performed a randomized double-blind clinical set-up that included healthy women without TMD as well as women with an earlier TMD history. Both groups were randomly divided into true and placebo interference groups.…”
Section: Temporomandibular Disorders and Occlusionmentioning
confidence: 99%
“…This monitor is important in this case because the study by Abe et al, 38 showed that the position of the main occluding areas (functional cusp) in the FPDs tended to be less stable; and some experimental evidence that small acute changes might provoke transient symptoms in subjects with a history of past TMDs. 39 In temporary cementation of definitive denture, record and observe the masticatory function in 1 week (Table 3). It can be seen that ROM, overbite, overjet and VDO are stable, no deflection, no pain in muscles and TMJs palpation, no pai in load testing.…”
Section: Discussionmentioning
confidence: 99%
“…Le Bell et al (2002) found that artificial interferences do not stimulate the development of dysfunctional symptoms in healthy subjects, instead they adapt successfully to them. In patients whose medical histories show TMD interferences stimulate the recurrence of stronger symptoms.…”
Section: Occlusion and Tmdmentioning
confidence: 99%